The Rhetoric of Village Heads in the 2023 Village Head Elections: Shaping Public Opinion in Babakan Losari Lor through Political Communication - Amalia Putri, Riza Qori; Setiansah, Mite; Nuryanti, Nuryanti (Technium Social Sciences Journal, 2024)
This study aims to analyze the local political dynamics in the village head election and to identify the rhetorical practices of the village head candidates in terms of ethos (credibility), pathos (emotional appeal), and logos (capacity and competence), which shape public opinion. A qualitative case study method was employed, involving participant observation, focus group discussions (FGD), and in-depth interviews with community members and the elected village head. Data collection included 10 informants: 9 community members and 1 village head. The results reveal that the elected village head effectively used ethos (credibility), pathos (emotion), and logos (logic) to influence voters. However, public opinion shifted after the election due to unfulfilled campaign promises, leading to dissatisfaction among some community members.